Hairy, scary, ordinary : what is an adjective? - Cleary, Brian P., 1959- (Cleary, Brian P., 1959- Words are categorical., 2000)
Rhyming text and illustrations of comical cats present numerous examples of adjectives, from "hairy, scary, cool, and ordinary" to "tan and tall," "funny, frisky, smooth, and small."